Poligami Dalam Konteks Perselingkuhan: Analisis Pasal 3 UU No.1 Tahun 1974 dan Maqashid Syariah - Solihat, Naysila Fitri; Arifin, Tajul (TAFAQQUH, 2025)
Polygamy remains a contested issue in Islamic family law, particularly when it intersects with infidelity. This study analyzes the regulation of polygamy under Article 3 of Law No. 1 of 1974 on Marriage through the lens of Maqashid Shariah, using a normative-empirical juridical approach. Primary legal sources include the Marriage Law, the Compilation of Islamic Law (KHI), Supreme Court Regulation No. 3 of 2019, and Maqashid Shariah principles. Secondary sources include reports from the Supreme Court (2023), LBH APIK (2022), and Komnas Perempuan (2021), alongside relevant academic literature. The findings reveal two central problems: first, legal loopholes in Articles 3–4 are systematically exploited to legitimize relationships originating from infidelity, particularly through the misuse of the "inability to bear children" clause without verified medical evidence; second, non-compliance with the principles of hifzh al-'ird (protection of honor) and hifzh al-nasl (protection of lineage) produces measurable harm to marital stability and children's welfare. This study recommends revision of the Marriage Law to establish operationally defined justice criteria, mandatory field verification by religious courts, and integration of Maqashid Shariah principles as substantive judicial standards.